2017
DOI: 10.1080/13607863.2017.1330873
|View full text |Cite|
|
Sign up to set email alerts
|

Intergenerational care: an exploration of consumer preferences and willingness to pay for care

Abstract: The results of this study show that there is demand for the shared campus and the visiting campus models among the Australian community. The findings support moves towards consumer-centric models of care, in line with national and international best practice. This consumer-centric approach is encapsulated in the intergenerational care model and enables greater choice of care to match different consumer demands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…The results showed a significant effect of yoga exercise and intergenerational interaction in experimental groups on general health scores and subscales of social dysfunction and depression compared to checks and pretests. These results are consistent with previous researchers ' findings that yoga exercises [13,20] and intergenerational interaction [21,22] are effective in improving health scales that are psychologically similar to anxiety, depression, and social functions. This finding is explained, yoga exercises can be said to increase physiological factors such as norepinephrine associated with alertness and dopamine associated with the pleasure mechanism, which has beneficial psychological effects of improving mood and cell activity, stress reduction, enhancement of the immune system improve attitudes towards oneself and life, increase self-esteem, energy and ultimately improve overall health [20].…”
Section: Discussionsupporting
confidence: 93%
“…The results showed a significant effect of yoga exercise and intergenerational interaction in experimental groups on general health scores and subscales of social dysfunction and depression compared to checks and pretests. These results are consistent with previous researchers ' findings that yoga exercises [13,20] and intergenerational interaction [21,22] are effective in improving health scales that are psychologically similar to anxiety, depression, and social functions. This finding is explained, yoga exercises can be said to increase physiological factors such as norepinephrine associated with alertness and dopamine associated with the pleasure mechanism, which has beneficial psychological effects of improving mood and cell activity, stress reduction, enhancement of the immune system improve attitudes towards oneself and life, increase self-esteem, energy and ultimately improve overall health [20].…”
Section: Discussionsupporting
confidence: 93%
“…7 Overall findings of the preliminary research demonstrated strong support for IPs and few legislative barriers that could not be overcome. 8,9 Therefore, the key objective of the Intergenerational Care Project was to prepare, trial and evaluate an intergenerational program within two models of care.…”
Section: The Intergenerational Care Projectmentioning
confidence: 99%
“…Through this research, two preferred models of care were identified: one model is a co‐location model, where aged care and childcare centres are located on the same property; the other model is a visitation model, where the centres are located separately and people from one centre are transported to the other centre . Overall findings of the preliminary research demonstrated strong support for IPs and few legislative barriers that could not be overcome . Therefore, the key objective of the Intergenerational Care Project was to prepare, trial and evaluate an intergenerational program within two models of care.…”
Section: Introductionmentioning
confidence: 99%
“…For the purposes of the development of the evaluation design and the identification of appropriate measures a clear understanding of an intergenerational program is important. In this paper an intergenerational care program refers to a specific type of program that involves the caring of older and younger people in a shared setting under the supervision of a formally trained caregiver (Vecchio et al, 2017). The program operates within a community setting.…”
Section: Aimmentioning
confidence: 99%
“…Previous investigation show that a rolling 8 week program works well (Golenko et al, 2020). The program characteristics were conceived from extensive consultations with a panel of experts using a Delphi technique and considered based on the practical and feasible implementation of the program within an Australian setting (Vecchio et al, 2017).…”
Section: Aimmentioning
confidence: 99%